Conformational Asn187Asp/Lys antithrombin variants and thrombosis - Picard, Véronique; Bauters, Anne; Khairy, Mahnouch; Ochat, Nadège; Jude, Brigitte; Aiach, Martine; Alhenc-Gelas, Martine (Thrombosis and Haemostasis, 2005)
Antithrombin Rouen VI (N187D) is a rare conformational thermolabile variant.The unique symptomatic carrier reported in the literature developed 3 thrombotic events during pregnancy, in each case in a context of pyrexial infection. In fresh plasma, antithrombin activity and antigen level were normal but in vitro experiments demonstrated the presence of a thermolabile variant, suggesting that fever could be a trigger for thrombosis in N187D carriers.The RouenVI variant was further found in two asymptomatic brothers. In these subjects, it was associated with normal antigen level but reduced activity. In order to better delineate the functional and clinical consequences of the N187 variants,we have studied a series of seven subjects from two distinct families heterozygous for the Rouen VI mutation. Antithrombin levels were normal or borderline in these patients. Thermostability of plasma antithrombin was normal. We have also studied six subjects heterozygous for a new mutation, 6462C>G,which results in an asparagine to lysine substitution at residue 187. In these patients, the N187K mutation is associated with a clear type II deficiency and decreased thermostability of the plasma protein has been demonstrated. That the N187D mutation has milder consequences on plasma antithrombin activity than the N187K mutation is in agreement with structural predictions. About 50% of the N187 carriers studied have suffered venous thrombotic events, strongly suggesting that both mutations are risk factors for thrombosis, but none occurred during pyrexial infections.
Keywords: Antithrombin; conformational variant; thrombophilia; serpin